Methodological support of the Estimated Efficiency of Public Procurement on a Contractual basis - T. M. Rogulenko; A. V. Bodyako; S. V. Ponomareva; P. A. Pashkov (Финансы: теория и практика, 2023)
The subject of the study is the problems of institutional and methodological-legal regulation of the contract system of public procurement.The relevance of the problem is due to the fact that there have been changes in the structure and composition of forms of contract activity as a result of the 2017 adoption of amendments to Law No. 44 in the dynamics of the distribution of order placement procedures.The purpose of the study is to develop a scientific methodology for calculating the effectiveness of procurement activities on the basis of a comprehensive assessment of the effectiveness of public procurement on a contractual basis, plan-fact analysis, and the implementation of the principles of compliance control in public procurement management.The paper uses methods of statistical and comparative analysis, generalization, classification and valuation. The paper shows that the present disadvantages of institutional regulation of procurement processes have a negative effect on their effectiveness, requiring improved oversight of public procurements as well as analytical and methodological support. The authors suggested that the principles of compliance-control of public procurement management be applied on a contractual basis in order to increase the level of credibility and legality of activities conducted in procurement. The author’s vision of the content of the methods of calculating the performance of procurement activities on the basis of a comprehensive evaluation of the effectiveness of public procurements on a contract basis is presented. For the collection of data for plan-fact analysis, their systematization for further calculation of performance indicators of public procurement on a contractual basis, a specialized form “Data Summary for Plan-Fact Analysis of Procurement” is proposed. If the procurement proposals presented in the study are implemented, they will increase the efficiency of the Russian public procurement contract system, the responsibility of participants in it, and the professional competence of officials.